2019
DOI: 10.1101/636530
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining the root endosphere and rhizosphere microbiomes from the World Olive Germplasm Collection

Abstract: Up to date, the bacterial and fungal microbial communities from the olive (Olea europaea L.) root systems have not been simultaneously studied. In this work, we show that microbial communities from the olive root endosphere are less diverse than those from the rhizosphere. But more relevant was to unveil that olive belowground communities are mainly shaped by the genotype of the cultivar when growing under the same environmental, pedological and agronomic conditions. Furthermore, Actinophytocola, Streptomyces … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Recently, the use of high-throughput sequencing allowed us to explore the composition and structure of microbial communities (fungi and bacteria) associated with olive cultivars from different geographical origins grown under the same climatic, agronomical, and pedological conditions [ 12 ]. Data revealed several interesting findings, making it possible to define a rather complete inventory of the rhizosphere and root endosphere microbiota (fungi and bacteria) associated with olive trees [ 12 ]. The results showed higher alfa diversity in the rhizosphere compared to that observed in the root endosphere.…”
Section: Advances In the Management Of Verticillium Wilt Of Olivementioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the use of high-throughput sequencing allowed us to explore the composition and structure of microbial communities (fungi and bacteria) associated with olive cultivars from different geographical origins grown under the same climatic, agronomical, and pedological conditions [ 12 ]. Data revealed several interesting findings, making it possible to define a rather complete inventory of the rhizosphere and root endosphere microbiota (fungi and bacteria) associated with olive trees [ 12 ]. The results showed higher alfa diversity in the rhizosphere compared to that observed in the root endosphere.…”
Section: Advances In the Management Of Verticillium Wilt Of Olivementioning
confidence: 99%
“…While previous studies revealed the importance of the geographical origin in building up the endophytic prokaryotic communities found in olive leaf tissues [ 185 ], our study concluded that the genotype, rather than geographical origin, is the main factor in shaping the olive belowground microbial communities. Moreover, the genotype is more determinant in the rhizosphere than in the root endosphere, and more crucial for the bacteriota than for the mycota [ 12 ]. The study also revealed that Actinophytocola was the most abundant genus inhabiting olive roots, followed by the genera Streptomyces and Pseudonocardia .…”
Section: Advances In the Management Of Verticillium Wilt Of Olivementioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the fungal endophytes colonizing the vegetative organs of olive tree were highly diverse (total of 205 OTUs), being most of the isolates belonging to phylum Ascomycota and class Sordariomycetes. Similarly, previous studies using both culturaldependent and -independent approach (Abdelfattah et al, 2015;Fernández-González et al, 2019) Germplasm Collection (in Spain). Without excluding the potential biases related to culture-dependent method , this variation on the most abundant genera in roots could be related with differences on sampling sites and sampling time, which were recognized to influence endophytic fungal assemblage in olive tree .…”
Section: Discussionmentioning
confidence: 81%